A Complaint Management System for Enhanced Efficiency at West Visayas State Univresity – Himamaylan City Campus: ISBN 978-630-95064-4-3 - Muzones, Edlin (Technium Books, 2025)
"A Complaint Management System for Enhanced Efficiency at West Visayas State Univresity – Himamaylan City Campus" ISBN 978-630-95064-4-3 is published in Technium.